INVESTIGATING EFFECTS OF PERCEIVED SERVICE QUALITY ON OVERALL SERVICE QUALITY AND CUSTOMER SATISFACTION: CASE OF SAUDI AIRLINES - Alsini, Ibrahim (Journal of Tourism, Sustainability and Well-being, 2017)
An increase in information readiness and intense competition between service organizations leads to more challenges in the business environment. On top of these service characteristics and need for a human touch are additional challenges for airline companies, not only to be successful but also to survive. Thus, knowing what airline customers think about an airline and gauging their satisfaction levels are of utmost importance. The aim of this study is to analyse the perceptions of service quality and levels of satisfaction among customers of the national airline of Saudi Arabia. To do so, it adopts the Airline Quality (AIRQUAL) scale. This scale comprises 44 items on seven distinct dimensions, namely; airline tangibles, terminal tangibles, personnel, empathy, image, perceived service quality, and customer satisfaction. Results of extensive data analysis support significant relationships with these study dimensions. Most notably, ‘Airline Tangibles’ are found to be the most influential factor creating a pool of satisfied airline customers. The text discusses the findings and implications of the survey.